PENGARUH STRUKTUR MODAL DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA USAHA KECIL DAN MENENGAH DI INDONESIA - Margaretha, Farah; ., Khairunisa (Manajemen Bisnis Kompetensi, 2016)
ABSTRACT The problem of this research was the small and medium enterprises (SMEs) have an important and strategic role in the Indonesian economy, it is important to know the factors that affect the profitability of SMEs. The objectives of this research were to determine whether there are influencesof capital structure (DER) and liquidity (CR) to profitability (ROA) and (ROE) on SMEs. The methodology of this research was multivariate linear regression analysis method. The samples were 57 SMEs which part of index Pefindo in 2010-2014. Finding and contribution in this research was showed that the capital structure of the significant negative effect on profitability (ROA), but the capital structure does not significantly influence (ROE). While liquidity has no significant effect on profitability in this case (ROA) and (ROE). Implication of this research was managerials have to increase their retained earning for operating cost and continue to improve its efforts in managing the companyÃ¢â¬â¢s capital structure as efficiently and effectively as possible in order to achieve the desired level of profitability, and use the retained earnings to reduce the use of a large debt from third parties for the companyÃ¢â¬â¢s operations. Keywords: capital structure, index pefindo, liquidity, profitability, small and medium enterprises